3-2n=13+3n

Simple and best practice solution for 3-2n=13+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2n=13+3n equation:


Simplifying
3 + -2n = 13 + 3n

Solving
3 + -2n = 13 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
3 + -2n + -3n = 13 + 3n + -3n

Combine like terms: -2n + -3n = -5n
3 + -5n = 13 + 3n + -3n

Combine like terms: 3n + -3n = 0
3 + -5n = 13 + 0
3 + -5n = 13

Add '-3' to each side of the equation.
3 + -3 + -5n = 13 + -3

Combine like terms: 3 + -3 = 0
0 + -5n = 13 + -3
-5n = 13 + -3

Combine like terms: 13 + -3 = 10
-5n = 10

Divide each side by '-5'.
n = -2

Simplifying
n = -2

See similar equations:

| 69c-(27c-51)= | | 4+(d+2)-2d=3(2+d) | | 7a^3+b^4= | | r+10=7t-14 | | -12-(-12)-4+(-6)= | | 19+52y-11+7=62 | | 7m+49+4m=137 | | 2x^3-42x^2+252x-352=0 | | 1360*0.45= | | 90x-9x^2-100=0 | | 0+12=12 | | -(t+1)= | | 15-21=-n | | .45x=62.49 | | 5(12-2e)=20 | | -10-(-9)-5+(-3)= | | 19x+5y=8 | | 11(2x-2)+8=74 | | 6x-54=-12x+36 | | -(x-75)= | | 3(4x+9)=75 | | 5(n-10)-7n=18 | | 2x+64=180 | | 7w^2-25=62 | | 6(3x+11)=3 | | -3x-10=6-2x | | 10x+4-2-3x=-12 | | 27+4y-9=17y-14-5y | | 7n+4=3n-8 | | 36w^2-25=62 | | 4(y+5)-3y+7=10 | | r^2-12r+35=62 |

Equations solver categories